COMAGMATIC GRANOPHYRE AND DACITE FROM KARYMSKY VOLCANIC CENTER, KAMCHATKA: EXPERIMENTAL CONSTRAINTS FOR MAGMA STORAGE CONDITIONS - Izbekov P.; Gardner J.E.; Eichelberger J.C. (My University, 2004)
Despite a ∼30 000 years difference in age, two caldera-forming eruptions at Karymsky volcanic center, Kamchatka – Karymsky (7900 yr BP) and Academy Nauk (ca. 40 000 yr BP) – produced two-pyroxene dacites with the same composition and mineralogy. Granophyric xenoliths of the identical whole-rock chemistry were found in basalts erupted within Academy Nauk caldera in 1996. Unlike the dacites, however, the granophyres are holo-crystalline and contain biotite and amphibole. Large amphibole phenocrysts contain rare inclusions of clinopyroxenes, which compositionally overlap with clinopyroxenes in the dacites. The Al content of the amphibole suggests it grew at a pressure of about 100 MPa. Results of hydrothermal experiments and petrologic observations indicate that Academy Nauk and Karymsky dacites were last equilibrated at 883±19°C, 100±15 MPa and 871±19°C, 85±18 MPa, respectively, both at water-saturated conditions. The mineral assemblage of granophyre is reproduced by isobaric crystallization of the dacite at 100 MPa, implying that the granophyres were sampled from the crystallized silicic reservoir that produced the caldera-forming eruption of Academy Nauk. Similar chemical compositions of Karymsky and Academy Nauk dacites indicate that both were derived from the same crustal-level source. The eruptive history of the calderas can best be explained by two 10–12-km3 dacitic batches that detached from a parental body situated in the lower crust, then ascended to 3–4 km depth, re-equilibrated, and erupted.
Keywords: dacite; granophyre; calderas; Kamchatka Peninsula; experimental studies; petrology